Big techs: a experiência humana como matéria prima do poder - Almeida, Erika Silva e Souza de (2023)
Over more than 20 years, big techs built their way towards economic and political power, while offering the most varied technologies, and countless advances. How they took root in power structures using human experience as raw material is the problem to be investigated by this research. The big techs make up the object, having their command and functioning structures as a corpus. The objective is to understand how they evolved from the use of information to improve products, to become a form of power that relativizes established powers. The hypothesis is that neoliberalism and its defense of the minimal State and the subject-company was the ideal context for big techs to become a new sovereign power, with consequences that we cannot yet measure. To support it, the investigation will be based on the communication processes studied from the concepts of sovereignty, discipline and biopower by Michel Foucault, and neoliberalism as a logic, by Dardot and Laval, in their confluences and divergences, and the concept of corpusmedia proposed in the Corpusmedia Theory (KATZ; GREINER). The methodology will consist of a bibliographic review and analysis of the corpus formed by big techs